Literature Review: Urban Poverty in a Sociological Perspective - Komang Ariyanto (Universitas Terbuka, 2023)
Poverty is a major problem that is a major concern for the government. The level of disparity in urban and rural poverty is very high, however poverty in urban areas remains a national poverty alleviation challenge. This writing aims to describe the phenomenon of poverty in urban areas based on a structural-functional perspective. This research uses a qualitative method with a literature study approach. Data collection was carried out through secondary data sourced from books, journals, the internet, official documents related to poverty and structural-functional theory. The findings in this paper are that poverty in urban areas has prevented children from receiving quality education, facing difficulties in financing health care, and limited fulfillment of their needs for food, clothing and shelter. Poverty alleviation efforts must be based on the determination of the appropriate poverty line and a clear understanding (definition of poverty in local parameters) regarding the causes of the problem. The recommendations/implications of these findings are expected to contribute findings/ideas to studies of urban development in Indonesia, especially sociological studies of poverty. In addition, recommendations for regional government intervention in formulating development policies that are more pro-poor in urban areas.